Alcohol and older people from a public health perspective - Peter Anderson; Emanuele Scafato; Lucia Galluzzo (Istituto Superiore di Sanità, 2012)
OBJECTIVES AND METHODS: As part of the European project VINTAGE, a systematic review of scientific literature was undertaken to document the evidence base on the impact of alcohol on the health and well-being of older people, and on effective policies and preventive approaches to face the problem in this steadily increasing segment of the population. RESULTS: 369 references were identified, from which 78 papers were selected. CONCLUSIONS: The review confirms the paucity of data on this topic and the need for more specific research. Although there is scarce evidence, the elderly seems to respond equally well to alcohol policy, screening instruments and brief interventions as do younger adults. According to a lifecycle approach, a future focus on the middle aged is also recommended.